2014
DOI: 10.1890/es14-00171.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feral free‐roaming horses on semi‐arid rangeland ecosystems: an example from the sagebrush steppe

Abstract: Abstract. Feral horses (Equus caballus) are viewed as a symbol of freedom and power; however, they are also a relatively unmanaged, non-native grazer in North America, South America, and Australia. Information about their influence on vegetation and soil characteristics in semi-arid rangelands has been limited by confounding effects of cattle (Bos taurus) grazing and a lack of empirical manipulative studies. We compared vegetation and soil surface characteristics in feral horse grazed areas and ungrazed exclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Increased numbers of horses are associated with negative impacts to arid and semi‐arid landscapes and some of the species inhabiting these environments (Beever , Beever and Aldridge , Davies et al. , Hall et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased numbers of horses are associated with negative impacts to arid and semi‐arid landscapes and some of the species inhabiting these environments (Beever , Beever and Aldridge , Davies et al. , Hall et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased numbers of horses are associated with negative impacts to arid and semi-arid landscapes and some of the species inhabiting these environments (Beever 2003, Beever and Aldridge 2011, Davies et al 2014, Hall et al 2016b). Horses can degrade habitat features (e.g., soil and vegetation) via trampling, excessive nutrient deposition, and overgrazing (Loydi and Zalba 2009, de Villalobos et al 2011, Parvage et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle are currently grazed at a fairly low stocking rate in the area, but feral horses are present in fluctuating abundance due to sustained population growth with periodic round‐ups as mandated by federal law (Public Rangelands Improvement Act ). Feral horses have been linked to a variety of negative effects on ecosystems (Davies et al ), and their apparent preference for certain wellpads in the area of our study may have prevented reclamation success or slowed successional processes.…”
Section: Discussionmentioning
confidence: 88%
“…Other studies have also found positive effects of horse grazing on floristic diversity in different plant communities like coastal and wet grasslands in France (Loucougaray et al 2004;Marion et al 2010). However, horse grazing can have negative impacts on plant diversity under more arid conditions, as found in rangelands in Nevada (Beever and Brussard 2000;Davies et al 2014). Greater increases in species density under horse grazing were found at 25-m 2 than at 1-m 2 quadrats.…”
Section: Plant Diversitymentioning
confidence: 82%